2007
DOI: 10.3171/spi-07/12/669
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral approach to the cervical spine: major anatomical structures and landmarks

Abstract: Object The authors undertook a study to explore the topographic anatomical features seen during the anterolateral approach to cervical spine, anatomical variations, and certain landmarks related to the surgical procedure. Methods The study was conducted in 30 fresh cadavers. Results The common carotid artery bifurcation was mostly found at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 32 publications
2
43
0
2
Order By: Relevance
“…Injury to the V 2 segment of the VA may occur during lateral dissection of the vertebral body (VB) with subperiosteal elevation of the longus colli muscles or lateral drilling of the uncinate process (18). The longus colli muscle is the longest and most medially located of the prevertebral muscles (4), located on the anterior aspect of the cervical spine and divided into a superior oblique, inferior oblique, and vertical parts (11). Reflecting or removing the longus capitis and longus colli muscles exposes the transverse process and vertebral artery (11).…”
Section: Introductionmentioning
confidence: 99%
“…Injury to the V 2 segment of the VA may occur during lateral dissection of the vertebral body (VB) with subperiosteal elevation of the longus colli muscles or lateral drilling of the uncinate process (18). The longus colli muscle is the longest and most medially located of the prevertebral muscles (4), located on the anterior aspect of the cervical spine and divided into a superior oblique, inferior oblique, and vertical parts (11). Reflecting or removing the longus capitis and longus colli muscles exposes the transverse process and vertebral artery (11).…”
Section: Introductionmentioning
confidence: 99%
“…The distance between musculi longus colli on both sides widens as it descends. Civelek et al 2 determined that the origin of the musculus longus capitis is the tuberculum anterius of the C3-6 in 57% and of the C3-7 in 43% of specimens. The musculus longus capitis can be retracted laterally over the musculus longus colli.…”
mentioning
confidence: 99%
“…Civelek et al 2 showed that 90% of the arteria vertebralis enters the foramen transversarium at the C-6 level, 7% enter at the C-5 level, and 3% enter at the C-4 level. This information should be considered before performing operations requiring wide anterolateral resection, such as a spondylectomy.…”
mentioning
confidence: 99%
“…The C4 level was verified with a transverse ultrasound projection of the bifurcation of the carotid artery at the right ventral side of the neck. The carotid artery is commonly observed at the C4 level (91). The transducer was then rotated to a longitudinal position and the ventral images were recorded in this position (Fig.…”
Section: Study Bmentioning
confidence: 99%
“…However, the C4 spinous process and vertebral column were used as reference points in the dorsal images and the bifurcation of the carotid artery (commonly at the C4 level) (91), in the ventral images. Another potential limitation was that the ROI was selected manually for each muscle.…”
Section: Validity and Limitations Of Ultrasoundmentioning
confidence: 99%